A chronicle of cultural transformation: ethnography of Badagry Ogu musical practices - Kunnuji, Joseph (College of Music, 2020)
This thesis examines the musical practices of Badagry Ogu people from both historical and contemporary perspectives and provides strategies for their further integration into the changing social and economic landscape characteristic of 21st-century Lagos. Badagry emerged as a Nigerian town bordering the Republic of Benin in the 19th-century colonial delineation processes, which neglected ethnic frontiers. Consequently, Badagry Ogu people, being a minority ethnic group and geographically peripheral in Nigeria, have been politically, economically and socially marginalized for generations. Using ethnographic methods in studying selected indigenous musical bands (Gogoke, Gigoyoyo, Kristitin and Akran Ajogan), a biographical sketch of master drummer Hunpe Hunga, and an applied ethnomusicology method of collaborative music composition and arrangement, I chronicle the musical heritage of Badagry Ogu people. In addition, I suggest an approach for its recontextualisation into different creative economies. I engage Thomas Turino's framework for identity and social analysis, including the concepts of cultural cohorts and cultural formations, in exploring the different attitudes, among Badagry Ogu people, towards indigenous music. I advocate for and outline a contemporary approach for musical recontextualisation as a means of inclusivity and economically empowering performers of indigenous Ogu music in Badagry. This thesis includes my additional arrangements to the studio recordings of Gogoke. The recontextualisation process, which commenced with Gogoke's recording of indigenous instruments and vocals in Badagry Lagos Nigeria, reached its full fruition in the overdubs of Western musical instruments in Cape Town, South Africa. To further explore the theme of inclusivity, I examine current gender practices in Ogu communities evident in the gendered musical practices of contemporary Badagry. With its indepth analysis of Ogu genres, musical instruments, gender issues and a framework for recontextualising African indigenous musics, this thesis, while filling the gap in the study of ethnic minorities in Nigeria, is a significant contribution of the nuanced artistic practices of Badagry Ogu people to African music scholarship.